PHENOTYPIC PECULIARITIES OF ANTIMULLERS HORMONE LEVEL AND ULTRASOUND PARAMETERS OF OVARRIES IN WOMEN OF REPRODUCTIVE AGE WITH POLYSTYSTIC OVARY SYNDROME - Анжелика Юрьевна Беглова; Светлана Ивановна Елгина (The Publishing House Medicine and Enlightenment, 2019)
The aim of the research - determine the presence of differences in antimullers hormone (AMH) and ultrasound parameters of the ovaries in women of early reproductive age with polycystic ovary syndrome (PCOS), depending on the phenotype.Materials and methods. 100 women of reproductive age with PCOS were included in the study. All patients underwent general gynecological, clinical, instrumental assessment. The statistical analysis was performed using the commercially available statistical software package.Results. We found that 53.0 % women had a major (A) PCOS phenotype. Ovarian reserve of women of early reproductive age with PCOS was statistically significantly different from women without PCOS. The AMH index in women with PCOS with the main (A) and non-androgenic (D) phenotypes corresponded to a high level, with anovulatory (B) and ovulatory (C) - to a normal level. Statistically significant differences among the main (A), anovulatory (B) and ovulatory (C) phenotypes were established in the AMH levels depending on the phenotype; ovulatory (C) and non-androgenic (D) (p < 0.05). There were no differences among the main (A) and non-androgenic (D), anovulatory (B) and ovulatory (C) phenotypes (p > 0.05). Ultrasound parameters of the ovaries in women with PCOS of the main (A), ovulatory (C) and non-androgenic (D) phenotypes were significantly larger compared to healthy women (p < 0.05). In anovulatory (B) phenotype, these indicators did not differ compared to the control group (p = 0.128). According to the ultrasound parameters of the ovaries, the main (A), ovulatory (C) and non-androgenic (D) phenotypes did not differ (p > 0.05). In the anovulatory (B) phenotype, the ultrasound parameters were lower than in the main (A), ovulatory (C) and non-androgenic (D) phenotypes (p < 0.05). Conclusion. The study of indicators of ovarian reserve in women of early reproductive age with PCOS is a promising direction that will allow to more accurately determine the reproductive potential of each particular woman and influence the choice of treatment tactics. The results obtained demonstrate the need to include the definition of ovarian reserve, primarily the level of AMH, in women of early reproductive age with PCOS as an additional diagnostic criterion for diagnosis and determination of further management tactics.